Crunch time: The optimal policy to avoid the "Announcement Effect" when terminating a subsidy - Marc Gürtler; Gernot Sieg (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2006)
We are considering for examination an Irreversible Investment under Uncertainty, subsidized by the government. If the government announces the termination of a form of subsidization, investors may decide to realize their investment in order to obtain the subsidy. These investors might have postponed an investment if future payment were assured. Depending on the degree of uncertainty and the time preference, the termination of said subsidy may cost the government more in toto than granting the subsidy on a continuing basis. We would like to show that a better strategy is to cut the subsidy in parts rather than terminate the subsidy in its entirety.
Keywords: H3; D11; 330; Irreversibility; Investments; Announcement effect; subsidies